Correlation of triglyceride glucose index with all cause mortality in acute myocardial infarction patients following percutaneous coronary intervention - Guang Yang; Zilun Huang; Shanjie Wang; Shuang Yang (Scientific Reports)
Abstract The Triglyceride glucose (TyG) index is a dependable indicator of IR, with numerous studies underscoring its influence on Cardiovascular disease. Nevertheless, the connection between the TyG index and prognosis in AMI patients after PCI is still uncertain. This investigation aims to explore the link in individuals who have received PCI for AMI. Upon admission, data regarding the patients’ age, sex, concurrent diseases, TyG index, and laboratory findings were meticulously documented. To discern the link between the TyG index and the 30-day and 12-month ACM, we employed a multivariate Cox proportional hazard regression model and K-M survival curve. The concordance evaluation was also enhanced by subgroup analysis. The investigation encompassed data from 1410 AMI patients who received PCI. The 30-day ACM rate was observed to be 15.1% (214/1410), while the rate at 12 months escalated to 26.0% (368/1410). Upon adjusting for potential confounders, multivariate analysis delineated a dramatic link between high TyG index and heightened mortality risk at both 30 days (HR 1.233, 95% CI 1.086–1.399) and 12 months (HR 1.127, 95% CI 0.963–1.318). According to K-M survival curve, patients presenting with higher TyG indexes demonstrated a noticeably higher probability of ACM within both the 30-day and 12-month. In AMI patients after PCI, the TyG index demonstrates a substantial link with ACM at 30-day and 12-month marks. This finding suggests the effectiveness of the TyG index in detecting AMI patients who are at a higher risk of mortality after undergoing PCI.